Validity of the 2014 traumatic encephalopathy syndrome criteria for CTE pathology. Issue 10 (7th April 2021) - Mez, Jesse; Alosco, Michael L.; Daneshvar, Daniel H.; Saltiel, Nicole; Baucom, Zachary; Abdolmohammadi, Bobak; Uretsky, Madeline; Nicks, Raymond; Martin, Brett M.; Palmisano, Joseph N.; Nowinski, Christopher J.; Montenigro, Philip; et al.
Abstract: Introduction: Validity of the 2014 traumatic encephalopathy syndrome (TES) criteria, proposed to diagnose chronic traumatic encephalopathy (CTE) in life, has not been assessed. Methods: A total of 336 consecutive brain donors exposed to repetitive head impacts from contact sports, military service, and/or physical violence were included. Blinded to clinical information, neuropathologists applied National Institute on Neurological Disorders and Stroke/National Institute of Biomedical Imaging and Bioengineering CTE criteria. Blinded to neuropathological information, clinicians interviewed informants and reviewed medical records. An expert panel adjudicated TES diagnoses. Results: A total of 309 donors were diagnosed with TES; 244 donors had CTE pathology. TES criteria demonstrated sensitivity and specificity of 0.97 and 0.21, respectively. Cognitive (odds ratio [OR] = 3.6; 95% confidence interval [CI]: 1.2–5.1), but not mood/behavior or motor symptoms, were significantly associated with CTE pathology. Having Alzheimer's disease (AD) pathology was significantly associated with reduced TES accuracy (OR = 0.27; 95% CI: 0.12–0.59). Discussion: TES criteria provided good evidence to rule out, but limited evidence to rule in, CTE pathology. Requiring cognitive symptoms in revised criteria and using AD biomarkers may improve CTE pathology prediction.